Serum Anguillae (Eel Serum) – An Updated and Comprehensive Materia Medica (Advancements in Homeopathic Research, 2024)
Introduction: Serum anguillae, derived from eel  serum, is a recent addition to the homoeopathic  materia medica with notable efficacy in renal, cardiac,  and hepatic conditions. Objective: This article provides an updated  materia medica, integrating clinical observations,  toxicological data, and pharmacological activities. Methodology:A systematic review of classical and  contemporary sources was conducted to compile this  materia medica. Results and Discussion: The remedy’s therapeutic  potential is explored, aligning traditional  homoeopathic uses with modern biomedical findings,  offering insights into broader clinical applications.  However, further reprovings can be considered to  explore the depth of remedy action.
Keywords: Zoological name; anguillae; clinical observations